Chemopreventive properties of phytosterols and maslinic acid extracted from coleus tuberosus in inhibiting the expression of EBV early-antigen in raji cells - Mooi, L.Y.; Wahab, N.A.; Lajis, N.; Ali, A.M. (John Wiley & Sons, 2010)
Bioassay-guided fractionation of a MeOH extract of tubers of Coleus tuberosus afforded the active anti-tumor-promoting compounds identified as the triterpenoid 2 alpha,3 beta-dihydroxyolean-12-en-28-oic acid (maslinic acid; CT2) and a phytosterol mixture (CT1). CT1 consists of stigmasterol (32%), beta-sitosterol (40.3%), and campesterol (27.7%) as determined by capillary gas chromatography. CT1 and CT2 showed very strong anti-tumor-promoting activities at IC(50) 0.7 mu g/ml and 0.1 mu g/ml, respectively, in a convenient, short-term in vitro assay, i.e., the inhibition of Epstein Barr virus (EBV) activation induced by phorbol 12-myristate 13-acetate (PMA) and sodium butyrate. We report for the first time the anti-tumor-promoting activity of 2 alpha,3 beta-dihydroxyolean-12-en-28-oic acid and show that a mixture of stigmasterol, beta-sitosterol, and campesterol is more potent than the individual components in inhibiting tumor-promoting activity.